Insurance-markets Equilibrium with a Non-convex Labor Supply decision, Unobservable Effort, and Incentive ("Fair") Wages - VASILEV, Aleksander (Journal of Mathematical Economics and Finance; Vol 5 No 2 (2019): JMEF, Volume V, Issue 2 Winter 2019, 2019)
The purpose of this note is to describe the lottery- and insurance-market equilibrium in an economy with non-convex labor supply decision, unobservable effort, and incentive ("fair") wages. The presence of indivisible labor creates a market incompleteness, which requires that an insurance market for employment be put in operation to "complete" the market.